2023
DOI: 10.3390/antiox12030727
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Perilla frutescens Extracts in Clinical Practice

Abstract: (1) Background: Perilla frutescens (L.) Britt. is an important pharmaceutical crop that remains a focus point for researchers worldwide due to its complex phytochemical constituents, medicinal effects, and nutraceutical properties. The literature data are based on animal and cell culture studies, so the clinical evidence for the therapeutic effects is poorly outlined. The aim of this review was to provide an updated and thorough understanding of Perilla frutescens applications in clinical practice using data d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Perilla frutescens (L.) Britt. (PF) is a prominent oilseed crop utilized as a source of edible vegetable oil, traditionally considered a health food in Asian countries such as Korea, China, and Japan ( 23 , 24 ). In comparison to other edible vegetable oils, perilla seed oil (PO) is primarily consists of PUFA (76 ~ 93%), ALA(57 ~ 62%) and LA(14 ~ 18%) ( 25 ), with ALA, an essential n-3 PUFA, being the most abundant ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perilla frutescens (L.) Britt. (PF) is a prominent oilseed crop utilized as a source of edible vegetable oil, traditionally considered a health food in Asian countries such as Korea, China, and Japan ( 23 , 24 ). In comparison to other edible vegetable oils, perilla seed oil (PO) is primarily consists of PUFA (76 ~ 93%), ALA(57 ~ 62%) and LA(14 ~ 18%) ( 25 ), with ALA, an essential n-3 PUFA, being the most abundant ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review outlined the main applications of Perilla frutescens in clinical practice using data derived from human studies and indicated that the extracts from this herb have demonstrated anti-inflammatory, antiallergic, antioxidant, and hypolipemiant effects in humans [ 30 ]. Other miscellaneous effects referred to its antibacterial and antifungal proprieties as well as its role as a prebiotic and reliever of gastrointestinal discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Perilla frutescens (known as perilla), a plant commonly consumed in many regions of Asia, contains complex phytochemical constituents, such as flavonoids, volatile oils, unsaturated fats, triterpenoids, and phenols [1,2]. Because of their multiple aromatic rings and several hydroxyl groups, the phenols in P. frutescens cause the plant to exert considerable antioxidant effects [2,3]. Perilla also exhibits potent anti-inflammatory properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation contributes to a microenvironment favoring the development and progression of various cancers, such as oral squamous cell carcinoma (OSCC) [5,6], renal cell carcinoma (RCC) [7], and colon cancer [8]. Because oxidative stress and inflammation are the causes of several pathological conditions, different parts of the perilla plant have long been used as traditional Chinese medicines to alleviate coughs, asthma, and constipation [2]. Hong demonstrated that perilla leaf extract (PLE) is a potent anti-SARS-CoV-2 agent that is capable of inhibiting SARS-CoV-2 replication [9].…”
Section: Introductionmentioning
confidence: 99%